Supporting data for the publication "Efficacy of mulch and tillage options to reduce runoff and soil loss from asparagus interrows" - Niziolomski, Joanna; Simmons, Robert W.; Rickson, R. Jane (Cranfield University, 2020)
In the UK, conventional asparagus cultivation practices on sloping land, erodible soils and increased frequency of extreme rainfall events combine to promote runoff generation and soil loss, particularly from interrows. This instrumented field study investigated the interactive effect of mulch and shallow soil disturbance (working depth of 0.175 m) on reducing runoff and soil loss.
Keywords: Asparagus'; 'Shallow soil disturbance'; 'Mulch'; 'Tillage'; 'Runoff'; 'Erosion'; 'Soil loss'; 'Physical Geography'; 'Soil Physics'; 'Surface Processes'; 'Agricultural Engineering'